Analysis of the Influence of Investment, Labor, and Infrastructure on Economic Growth in Indonesia - Yudi Budi Yuniarso; Sugiyanto (PT. Publikasiku Academic Solution, 2026)
Indonesia, as the largest economy in Southeast Asia, has experienced various economic dynamics following the COVID-19 pandemic, including fluctuations in investment, employment, and infrastructure development. This research analyzes the influence of investment, labor, and infrastructure on Indonesia’s economic growth during the 2020–2025 period. Using secondary data from BPS and related institutions, this study applies descriptive and quantitative analysis. The results show that foreign direct investment increased by 12.7% in Q1 2025, reaching Rp230.4 trillion. The labor force participation rate rose to 69.30% in 2023. Government infrastructure allocation reached Rp423 trillion in 2024, representing an 8% increase from the previous year. All three variables are positively correlated with economic growth, which reached 4.87% in Q1 2025. The interaction among these three variables creates synergy that drives economic growth through a multiplier effect, whereby infrastructure investment increases labor productivity, which in turn attracts further investment and creates a positive cycle for economic development. In conclusion, investment plays a strategic role in increasing production capacity and job creation; labor force participation continues to improve, although it still faces quality-related challenges due to the dominance of the informal sector; and infrastructure development reflects the government’s strong commitment despite the persistent infrastructure gap. The study recommends improving investment quality, strengthening labor training, and accelerating infrastructure development to support national economic targets.